2017
DOI: 10.1097/pts.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Patient Safety

Abstract: To our knowledge, this is the first methodological review of racial/ethnic disparities in patient safety in the United States. The evidence on the existence of disparities in adverse events was mixed. Poor stratification of outcomes by race/ethnicity and consideration of geographic and hospital-level variations explain the inconclusive evidence; variations in the quality of care at hospitals should be considered in studies using national databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…• There was no significant difference between African Americans and Caucasians for infection rate associated with total hip replacement. Okoroh et al [ 59 ] 2017 US Setting not applicable Systematic review n = 24 Ethnic minorities a) Explore differences in reporting race/ethnicity in studies on disparities in patient safety assess adjustment for socioeconomic status, comorbidity, and disease severity • Eight studies included race/ethnicity in baseline characteristics and adjusted for confounders. • Hospital-level variations were infrequently analysed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…• There was no significant difference between African Americans and Caucasians for infection rate associated with total hip replacement. Okoroh et al [ 59 ] 2017 US Setting not applicable Systematic review n = 24 Ethnic minorities a) Explore differences in reporting race/ethnicity in studies on disparities in patient safety assess adjustment for socioeconomic status, comorbidity, and disease severity • Eight studies included race/ethnicity in baseline characteristics and adjusted for confounders. • Hospital-level variations were infrequently analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Baehr et al and Okoroh et al in their systematic reviews also noted increased risk of certain ADEs among certain ethnicities for some drugs and contributed these to genetic predisposition and overuse [35,59]. Five systematic reviews concerning adverse events in surgical patients and ADEs were also included [35,37,56,58,59]. In their systematic review and meta-analyses of 26 studies relating to complications and mortality in surgical care, Bloo et al found that ethnic minorities have a higher risk of complications in perioperative care as compared to the ethnic majority patients resulting in a higher incidence of pain and re-operation [37].…”
Section: Review Q 2: What Is the Evidence For Patient Safety Events Imentioning
confidence: 97%
See 2 more Smart Citations
“…The 2014 Nation Action Plan has recognized that certain populations might bear a disproportionate burden of ADEs, and it calls for a better understanding of these potential disparities. While other literature reviews have examined racial or ethnic disparities in ADEs, these reviews have been limited by the inclusion of few studies [48] or the focus on a single medication class [49]. To our knowledge, this is the first systematic literature review to examine the state of evidence for racial or ethnic disparities in ADEs, both in general and with particular emphasis on the high-impact drug classes as outlined in the 2014 National Action Plan.…”
Section: Discussionmentioning
confidence: 99%